2021
DOI: 10.7717/peerj.12591
|View full text |Cite
|
Sign up to set email alerts
|

Self-stigma and cognitive fusion in parents of children with autism spectrum disorder. The moderating role of self-compassion

Abstract: Background Research shows that people with autism spectrum disorder and their families often experience social stigma. The internalization of social stigma can lead to the occurrence of self-stigma, understood as an internalized cognitive-affective self-directed and rigid process that results in individuals agreeing with stigmatizing opinions and applying them to themselves. Experiencing self-stigma can lead to a cognitive fusion with negative thoughts–especially those about oneself. Previous studies show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Thus, the potential mediating and moderating mechanisms behind these associations in people seeking trauma care services also require further investigation to understand how to better address the potential impacts of self-stigma. For example, a previous study found that self-compassion may buffer the effects of self-stigma on cognitive fusion (Pyszkowska et al, 2021 ). The psychoeducation programme in the present project (the evaluation results have been reported elsewhere (Fung, 2021 ; Fung, Chan, et al, 2022 ) as well as in the Supplementary Table S3) might also be a promising way to address self-stigma in trauma survivors, as the levels of self-stigma reduced after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the potential mediating and moderating mechanisms behind these associations in people seeking trauma care services also require further investigation to understand how to better address the potential impacts of self-stigma. For example, a previous study found that self-compassion may buffer the effects of self-stigma on cognitive fusion (Pyszkowska et al, 2021 ). The psychoeducation programme in the present project (the evaluation results have been reported elsewhere (Fung, 2021 ; Fung, Chan, et al, 2022 ) as well as in the Supplementary Table S3) might also be a promising way to address self-stigma in trauma survivors, as the levels of self-stigma reduced after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Ao mesmo tempo, técnicas cognitivo-comportamentais como a autocompaixão desenvolvem efeitos protetivos à saúde mental e devem ser incentivadas ao cuidado das mães de crianças com SCZ. A autocompaixão implica em olhar atento para consigo mesmo, reconhecendo suas limitações enquanto condição humana, aprendendo a conviver com as dificuldades e manuseando práticas bondosas para si (22) . Cabe as Enfermeiras planejar cuidados que integrem as três propriedades da autocompaixão: bondade própria, humanidade comum e atenção plena.…”
Section: Discussionunclassified
“…These MHPs can then have greater choice of action. Although cognitive fusion was found to be associated with affiliate stigma and depression in parents having children with autism spectrum disorder (Pyszkowska et al, 2021), further research is needed to determine its relevance in MHPs and its function in the process of internalizing occupational stigma. Therefore, the present study aimed to explore the role of cognitive fusion in modifying the effect of affiliate stigma on occupational stigma and emotional distress in MHPs.…”
Section: Occupational Stigma In Mhpsmentioning
confidence: 99%